The role of community education in China in the transmission of traditional culture: a systematic literature review - Chen, Zhuo; Hassan, Aminuddin; Ghazali, Siti Sabihah (Human Resources Management Academic Research Society (HRMARS), 2024)
As globalization progresses, the preservation and transmission of traditional cultures become critically important. Community education plays a significant role in cultural heritage, particularly in China, a multi-ethnic nation emphasizing the importance of inheriting and promoting ethnic cultures within the framework of constructing a modern civilization for the Chinese nation. This study aims to systematically review and analyze the existing literature on the application and effectiveness of community education in the transmission of traditional Chinese culture. By synthesizing both domestic and international research, it identifies key factors influencing the effectiveness of cultural transmission through community education and optimizes strategies for future implementations. The author reviewed articles published between 2004 and 2024, using databases from CNKI, and relied on peer-reviewed and online accessible journals for this paper. Despite challenges like resource and policy limitations, community education remains an effective mechanism for preserving and transmitting culture. The recommendations proposed in this study aim to enhance the implementation of community education, support the ongoing preservation and transmission of culture, and inspire practitioners and researchers in the same field.